2013
DOI: 10.4236/ojbd.2013.33018
|View full text |Cite
|
Sign up to set email alerts
|

SNPs and TFBS Associated with High Altitude Sickness*

Abstract: The rSNPs for the genes AKT3 (rs4590656), EGLN1 (rs480902), eNOS3 (rs1007311), and VEGFA (rs699947, rs13207311, rs1570360, rs2010963) have been significantly associated with the physiological parameters in high altitude sickness Han or Tibetan Chinese patients at the Qinghai-Tibetan plateau. The alleles of each rSNP have been found to create unique transcriptional factor binding sites for transcription factors that affect the process of hypoxia gene expression in this high altitude hypoxia environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 49 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…Prior et al suspected an interaction with the HRE based on their location in the same DNA region [84,89] and speculated about a potential role of the SNP À1154 A/G and the interaction with the HRE under participation of the SNP +405 C/G [84]. Aside, an impact of TFBS for the SP-1 and ZNG354C was hypothesized [50]. Additionally, we could identify various potential TFBS (Table 3), making the situation more complex.…”
Section: Snp à1154 A/gmentioning
confidence: 94%
See 2 more Smart Citations
“…Prior et al suspected an interaction with the HRE based on their location in the same DNA region [84,89] and speculated about a potential role of the SNP À1154 A/G and the interaction with the HRE under participation of the SNP +405 C/G [84]. Aside, an impact of TFBS for the SP-1 and ZNG354C was hypothesized [50]. Additionally, we could identify various potential TFBS (Table 3), making the situation more complex.…”
Section: Snp à1154 A/gmentioning
confidence: 94%
“…In studies investigating high altitude sickness, the identified TFBS for GABP alpha and an additional TFBS for IF1 could be described for +405 C-allele and Sp-1 binding site for +405 G-allele [50].…”
Section: Snp +405 G/cmentioning
confidence: 98%
See 1 more Smart Citation
“…Some of these SNPs have been examined in association with high-altitude sickness (HAS) among Han and Tibetan Chinese at the Qinghai–Tibetan Plateau in China 1620. Recently, the association of SNPs that create potential changes in transcriptional factor binding sites (TFBS) and HAS have been examined 20,21. To this end, punitive changes in TFBS have been reported to be created by 17 SNPs among nine genes significantly associated with acute mountain sickness (AMS) in Han Chinese 20.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, the relationship between LD, SNPs, and TFBS can be used to identify potential gene regulatory TF binding changes, which could result in disease or sickness. [14][15][16][17][18][19][20][21] In this report, LD will be considered as the non-random association of SNP alleles within the gene. The purpose of this review is to highlight some of these genetic associations for 6 genes involved in known human diseases and sicknesses that have been recently studied.…”
Section: Introductionmentioning
confidence: 99%